(untitled) (Research, Society and Development, 2021)
The study it consisted of evaluating the effect of the inoculation and reinoculação of strain ZAE94 of Herbaspirillum seropedicae in two varieties of rice. The efficiency was evaluated by the contribution of these bacteria in the agronômicos parameters of production of grains, N%, N-total and rude protein of the grains in the varieties of rice IR42 and IAC4440. The inoculation experiment was lead block-type to perhaps with six repetitions. For the reinoculation experiment, the evaluated variable had been similar to the previous experiment, being that the aerial part of the remaining plants of rice was removed and the remain of the plants was incorporated the ground. The inoculation of lineage ZAE 94 was capable to supply up to 50 kg of N ha-1 depending on used cultivating. Effect of the reinoculation on the parameters studied in the tested conditions was not observed, indicating that the inoculation must be made in all the planting. The results had revealed promising how much to the use of the practical one of inoculation in the culture of the rice.